LITERATUR REVIEW : MINAT MEMPELAJARI FISIKA DAN HUBUNGANNYA DENGAN MISKONSEPSI MAHASISWA PADA FLUIDA STATIS - Nadia Alfia Netta (JURNAL SPEKTRA, 2021)
This research is a literature study with descriptive qualitative research type with library research which seeks to describe the interest in studying physics and its relationship with students' misconceptions on static fluids. However, in fact, one of the problems found was the low interest of students in learning physics, causing students to lack understanding of the concepts in learning physics, resulting in low student learning outcomes. In this literature study research the authors use various written sources such as articles, journals and relevant documents. Based on the studies that have been obtained, it states that the more interested students are in a concept that is being studied, the less likely it is that misconceptions will arise. Lack of interest in physics causes students to be reluctant to understand concepts, leading to misconceptions. Misconception refers to concepts that are incompatible with the scientific understanding accepted by experts. Misconception problems and student interest in learning are not easy to solve. Based on these conditions, for misconceptions it is very important to do a diagnostic test on students' conceptual understanding, one of which is by using a Four-Tier Diagnostic test and for interest a test is carried out using an interest questionnaire.